Vloga Zavoda za gozdove Slovenije pri povezovanju lastnikov na lokalnem nivoju - Medved, Mirko (Gozdarski vestnik, 2006)
The Slovenian forest development programme from 1996 and the European Forest Action Plan from 2006 both stress the importance of cooperation between forestowners for future sustainable forest management. The purpose of the article is to determine how foresters of the Slovenian Forest Service evaluatepossibilities for improving cooperation between forest owners on the local level. An analysis of strengths, weaknesses, opportunities and threats has been made via inquiry. Field foresters were asked how they see their organisation as a promoter of cooperation between forest owners. The number ofanswers in different parts of the SWOT analysis is in positive correlation with the level of education. Job, sex and average forest property do not significantly influence the number of answers. The most important strengths ofSFS are knowing the owners, space covering and staff competences. Main weaknesses are low motivation, staff shortage and poor cooperation between different levels of relevant institutions. Opportunities are: more education and information for owners achieved by better cooperation between institutions, improved help from the state and communities as well as better organisation of marketing and wood promotion. Threats are recognized in unsuitable state and local policy, uninterested owners and in the continuous fragmentation of forest properties. Results acquired from the majority of field foresters are a good foundation for forming strategic plans for more intense management of private forests. Research should be repeated periodically.
Keywords: zasebni gozdovi; lastniki; Slovenia; Slovenija